Sobre el discurso de los derechos humanos en tiempos de pandemia - De Asís Roig, Rafael (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2023)
It is not possible to say that there were good times for human rights before the pandemic produced by Covid-19. And it is evident that this pandemic has lowered the degree of satisfaction of human rights. The world faces levels of poverty and inequality that will put legal-political systems in tension. And this tension will also be present in what we can call the theoretical discourse of rights. A discourse that, as it is intended to account in this work, has suffered strong tensions during the pandemic, both in what has to do with the values that govern it and in what refers to the principles of organization that constitute its framework.